Marketing Strategy Plan Through SWOT Analysis On BLP Beauty's Expansion Into The French Market - Nayla Najwa Nafila (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to design a marketing strategy for BLP Beauty in the context of expansion into the French market through a SWOT analysis approach, supported by STEEP analysis, Customer Journey Map (CJM), and a 4P Marketing Mix framework. The internal analysis reveals that BLP Beauty excels in value-driven digital campaigns and sensory experience-based product innovation, yet needs to address weaknesses in inconsistent quality control and packaging. From an external perspective, the brand's primary opportunities stem from the high willingness to pay among French consumers and the potential for international strategic partnerships, while the main challenges include strict European Union regulations and consumer selectivity regarding product ingredients.